What impact has tendering had on trainees? Results of a national survey by British Association for Sexual Health and HIV Trainees' Collaborative for audit, research and quality improvement projects. (January 2018) - Wiggins, Helen; Hartley, Anna; Clarke, Emily; Foley, Elizabeth; Nandwani, Rak; Carlin, Elizabeth; Waters, Laura; Ahmed, Nadia
In April 2013, local authorities gained responsibility for commissioning sexual health services in England. With many services going out to tender and resultant change in services or service provider, there is anecdotal evidence that this has impacted on the education, training and morale of genitourinary medicine (GUM) trainees. The aim of this study was to evaluate the impact of tendering on GUM trainees. An electronic survey designed by the British Association for Sexual Health and HIV Trainees' Collaborative for Audit, Research and Quality Improvement Projects (T-CARQ) was distributed to GUM trainees and newly appointed consultants. Eighty-two individuals responded (74% GUM trainees, 25% newly appointed consultants, 1% locum appointed for service). Sixty-three per cent (45/72) had experience of training within a service which was being tendered. Of these, 59% (24/41) felt their training was not considered during the tendering process and 20% (8/41) felt that it was. Forty-four per cent (18/41) felt adequately supported. Thirty per cent (12/40) reported active participation in the tendering process. On a scale of 0 (no impact) to 5 (major impact), the median score for impact of tendering on training was 2. The positive/negative impact of tendering on different training elements was rated: other than management experience the overall impact on all parameters was negative, namely morale, senior support and education. In conclusion, this survey describes the variable impact of service tendering on GUM training. Our recommendations for maintaining training standards despite tendering include actively involving trainees and education partners, inclusion of specialist GUM training in service specifications, development of guidance for commissioners and services for the management of GUM training within tendering.